HUBUNGAN PENGETAHUAN PERAWAT TENTANG UNIVERSAL PRECAUTIONS DENGAN PENERAPAN UNIVERSAL PRECAUTIONS PADA TINDAKAN PEMASANGAN INFUS - Indra ' Syahrizal; Darwin Karim '; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purpose of this research was to know the relationship of nurses knowledge about universal precaution with universal precautions application in infusion action. This research used descriptive correlation methods with cross sectional approach. This research was conducted at RSUD Indrasari Rengat with 85 respondents. This research used total sampling technique. Measuring instrument of this research used questionnaire and observation sheet. The analysis used univariate and bivariate are using chi-square test. The results showed that there is the relationship of nurses knowledge about universal precaution with universal precautions application in vein insertion with p value 0,011. The results of this research recommends to the hospital to promote the importance of the application of universal precautions methods in nursing care to minimize the risk of infection in hospital Keywords: knowledge, nurses, universal precautions application, vein insertion.